The Translation Method of Figurative Language in 'The Tortured Poets Department: The Anthology Album' by Taylor Swift - Izzatul Fardiyyah; Moh Supardi; Hilmi Akmal; Sholikatus Sa’diyah (Journal of Translation, Linguistics and Literature, 2025)
This research aims to identify and analyze the types of figurative language found in the lyrics of Taylor Swift’s album The Tortured Poets Department: The Anthology, and to examine the translation methods used in the Indonesian version of the lyrics. The study applies the theory of figurative language by M.H. Abrams and the translation methods by Peter Newmark. The researcher uses a qualitative method, with data collected from the original English lyrics and their Indonesian translations on the BlinkBox Music website. The analysis focuses on five selected songs from the album, chosen purposively based on the richness of figurative expressions. The findings indicate that hyperbole appears most frequently, followed by personification, simile, metaphor, and others. Regarding the translation methods, literal translation is the most commonly used, followed by semantic, communicative, and then both faithful and free translation, which occur with equal frequency. The study concludes that the translator tends to preserve the original structure and meaning, but at times adapts expressions to be more culturally acceptable or emotionally resonant for Indonesian audiences.